(untitled) (Jurnal Bahasa, 2022)
This article discusses how the conversational style of children has been influenced by the multimedia device that is the computer. It shows that computers help children converse and also influences their conversational style. The children’s conversations were recorded and analysed using the Conversational Style Theory based on a list of 20 basic positive utterance. As a result of stimulation by computers, children are seen to produce conversation styles and able to handle communication situations. The analysis also proved that children have their own conversational style. It is hoped that this study will provide a little more information about the conversational style among children that results from the stimulation provided by computers.